Functional Organization of the Plant Nucleus - Meier, Iris (Plant Cell Monographs,, 2009)
While the cell nucleus was first identified in a plant, we know now far less about the plant nucleus than we know about its equivalent in animals or in fungi, because the field of nuclear biology has been predominantly driven by the non-plant model systems. More recently, however, plant biology has begun to catch up as research groups worldwide actively address the processes that define the plant nucleus. This volume is an up-to-date compilation of the multiple facets of this emerging discipline and presents the timely topic of functional organization of the cell nucleus entirely from the plant biologist's perspective. In a time of soaring food, fibre and energy needs, the understanding of the molecular mechanisms of plant genetic organization - and its effect on plant growth and development - is essential.